MUTUAL INFLUENCE AND MUTUAL ENRICHMENT OF THE RUSSIAN AND UZBEK LANGUAGES - Saidova Moxira Rasulevna (Galaxy International Interdisciplinary Research Journal, 2024)
The article examines the morphological systems of the Russian language in comparison with the native language. Parts of speech in Russian and Uzbek languages, principles of their classification. The presence of formal features of parts of speech. Interrelation and inter-transition of parts of speech in compared languages. The manual provides methods for word formation of parts of speech in the Russian and Uzbek languages. Their originality and degree of productivity.